Coping Strategi Keluarga Pemulung Dalam Pemenuhan Kebutuhan Dasar di Tpa Air Sebakul Kota Bengkulu Pada Masa Pandemi Covid-19 - Mirna Yunita; Warsa Sugandi Karman; Aprianto Soni; Nurmintan Silaban; Muhammad Alfi; Dedi Guntar (Universitas Prof. Dr. Hazairin, S.H, 2022)
This study aims to describe the coping strategies for scavenger families in meeting basic needs during the Covid-19 pandemic at the Air Sebakul TPA, Sukarami Village, Selebar District, Bengkulu City. This study used descriptive qualitative method. Data collection techniques were carried out by means of observation, interviews and documentation studies. This study involved 11 people as informants who were selected using purposive sampling. In fulfilling the clothing needs of 11 informants before the Covid-19 pandemic, they were still met, but during the Covid-19 pandemic, of which only 2 informants applied the Coping Strategy of Seeking Social Support and 9 other informants applied the Coping Strategy of Planful Problem Solving. To fulfill food needs, 11 informants applied Coping Strategy Planful Problem Solving. However, in meeting the educational needs of children from 11 informants, only 2 informants were able to meet the educational needs of their children and 9 other informants were not fulfilled. The recommendations of this research are addressed to the Bengkulu City Sanitation Office, which should continue to improve waste management, so that it can help scavenger families in achieving a better standard of living.